Mårten Stenberger - Jensen, O. Klindt (Kuml, 1961)
MÅRTEN STENBERGER. Professor Mårten Stenberger, whom Jysk Arkæologisk Selskab is honouring with the Worsaae Medal, is as familiar with Danish antiquity as with Danish archaeologists. He started an active and cordial cooperation with them as early as 1932 in Greenland, as Poul Nørlund's collaborator. Later, in 1939, this time as a member of a joint Nordic team, he excavated Icelandic house sites, which had been destroyed by Hekla. Not least, he deserves our gratitude for rescueing the publication of this material from the storms of the Second World War. When these had subsided, he took up with perseverance another great Scandinavian project, the investigation of Vallhagar on Gotland. This task was characteristic of him as investigator and man. The extensive Iran Age village, with fields and burial sites, was an excellent objective for groups of archaeologists, who although they were able to work independently, were nevertheless always in contact with one another. For himself he chose the tiresome job of providing for the maintenance of the excavators and the investigation, and was always ready with skilled advice and stimulating discussion. No wonder many Scandinavians became good friends during these campaigns. The test of the accomplishment of the field-work at Vallhagar, as in the investigations, was in the final publication. Here Mårten Stenberger's sure style makes its mark; the material is presented in full, illustrated with precision, discussed with deference to many different views and exploited for cultural history, even natural and geographical conditions being drawn upon to give a broad perspective. This precision, intensive study and an awareness of the demands of publication, have benefited other topics. One has only to consider his investigation of the Gotlandic material, the large Stone Age burial site in Vesterbjärs and the profusion of finds from the Viking Age (two thick volumes on this subject alone). His first major work, "Öland under äldre järnåldern", which in 1933 earned him his doctorate, is already a classic in Nordic archaeology. But we should not forget that Mårten Stenberger as professor at Uppsala, is in the middle of his research, stimulating and full of life, ever ready to take up new problems and to sally forth into the field with his diminutive tent, only just large enough to afford him protection. He is a true archaeologist, who enjoys being close to the earth and investigating its secrets. He lacks neither the tense anxiety of the excavator, nor the ironical self criticism, which are true attributes of a highly respected scholar. Ole Klindt-Jensen.